Influence of biomass fly ash on hydration and carbonation of cementitious materials - Teixeira, E. R. (2019)
Biomass fly ashes (BFA) properties allow their utilization as an alkaline material and good results are obtained when they are incorporated in concrete. Its utilization can minimize problems associated with cement production and with ash management. An experimental investigation was conducted to study the hydration and carbonation of cementitious materials with biomass fly ash. In this study BFA was incorporated on the weight of binder to produce some cementitious pastes and the hydration and carbonation of those pastes were studied. The results obtained show that BFA has a similar behaviour on the hydration of pastes than coal fly ash that is the pozzolanic material most used worldwide. Moreover, its utilization gives alkalinity to the paste mixtures that minimizes the carbonation effect. Thus, it seems